Dynamic Epidemiological Models for HIV/AIDS Associated TB Transmission: A Review (Journal of Informatics and Mathematical Sciences, 2025)
An extensive literature review suggests a significant link between HIV/AIDS and other diseases such as Pneumocystis pneumonia (PCP), Candidiasis, Cryptococcal meningitis, Toxoplasmosis, and Tuberculosis (TB). Here, our emphasis is on the HIV/AIDS associated Tuberculosis (TB) transmission dynamics. Since the last decade, due to the advancement in machine languages and neural networking, researchers have developed mathematical models to predict and investigate the dynamics of transmission of HIV/AIDS linked Tuberculosis (TB) globally. It includes the therapeutic aspects, like antiretroviral drug screening and treatment factors, in the study. We aim to cover the diversity of developed models to address the numerous key issues of the infection dynamics and provide the status of current and developed models to the global scientific community. Hence, it would help to build highly accurate future models to track the actual dynamics of the concerned disease. In this paper, we discussed deterministic modeling for the HIV/AIDS mediated Tuberculosis (TB) infection dynamics. Additionally, the threshold behaviour and the extended effect of mediations have been discussed. We conclude with an outline of the utilizations and accomplishments of HIV/AIDS-TB modeling and some proposed future directions.